Pemenuhan Nafkah Keluarga terhadap Suami Pemburu Babi di Nagari Malalak Utara dan Dampaknya terhadap Keutuhan Rumah Tangga - Ifdal Hamdi; Arsal (AHKAM, 2026)
Although baburu babi has long been part of the social activities of the Minangkabau community, studies examining its relationship with family maintenance and marital stability from the perspective of Islamic Family Law remain limited. This study aimed to analyze the provision of family maintenance by husbands who engage in pig hunting and the impact of baburu babi activities on marital stability in Nagari Malalak Utara. This field study employed a descriptive qualitative approach involving four informants, including three wives whose husbands participated in baburu babi activities. Data were collected through observation, interviews, and documentation and were subsequently analyzed descriptively and analytically using deductive, inductive, and comparative reasoning. The findings showed that, for some husbands, baburu babi activities constituted a source of income used to meet basic needs, children’s educational expenses, and household needs, although the income earned was irregular. These activities could also reduce time spent together, attention, and affection and cause anxiety among wives. In some families, these circumstances did not lead to divorce because they were supported by communication and trust, whereas in certain cases, they triggered disputes that ultimately resulted in divorce. This study concludes that baburu babi activities have varying economic and relational implications for family life. These findings extend the scholarship on Islamic Family Law by connecting maintenance obligations, sociocultural activities, and marital stability within the context of local communities.